Service Users’ Perspectives of a National Social Prescribing Programme to Address Loneliness and Social Isolation: A Qualitative Study - Thompson, Jill; Holding, Eleanor; Haywood, Annette; Foster, Alexis (Health & social care in the community, 2023)
Loneliness is considered to be a global public health challenge, impacting a range of physical and mental health conditions. Social prescribing, whereby service users are signposted into community-based activities and social groups by a community link worker, has been suggested as one mechanism to reduce service users’ loneliness and social isolation. This paper reflects on service users’ experiences of accessing a national social prescribing scheme. Drawing on qualitative findings from interviews with service users who were receiving support through a social prescribing programme between October 2017 and December 2018 (n = 26, with n = 12 interviewed a second time), we reflect on their experiences of the programme. We consider some of the complexities of providing short-term support with a focus on signposting people into local activities, when many service users prefer the companionship of their link worker. Furthermore, we highlight some of the difficulties in ending short-term support. Crucially, we highlight the importance of considering the intersection of the social determinants of health. We suggest that social prescribing schemes may exacerbate inequalities if consideration is not given to the ways in which people are (dis)advantaged in accessing the social capital necessary for their initial and continued involvement.